Solar LED based traffic light - Syamsul Rais, Ahmed Tazalli (2010)
Solar traffic light is the new technology providing a reliable, inexpensive, affordable and environmentally friendly source for modern traffic management systems. These “green” lights will also to help reduce electric energy usage. With no trenching, wiring or electrical work required, solar powered traffic lights are perfect for road safety and traffic control applications. Solar traffic lights are fitted with the latest technology in electronics. They are based on photovoltaic or PV for short. A solar panel which is located on the top of the pole converts sunlight into electrical power. A solar charger regulates the voltage coming out of the solar panel. The regulated power obtained is used to charge a battery. During daytime, the traffic lights can use voltage direct from solar panel. At the same time, the battery can be charge for using at night. Lighting is produced by arrays of extra bright LEDs that are much brighter than bulbs. LED last for years and is very energy efficient. LEDs are small, but it can produce a significant amount of light. Solar powered traffic lights and solar traffic signs are becoming more and more widespread around the world because they are portable, easily deployable, energy efficient, good for the environment and require minimum maintenance. One of the biggest problems in developing countries is power outages. An obvious advantage of solar traffic lights is that they will continue working as their main purpose is to keep traffic flowing even during power cuts. Solar directional signals and solar street lights offer an interesting and practical solution.